1996
DOI: 10.1007/s004270050058
|View full text |Cite
|
Sign up to set email alerts
|

The spalt-related gene of Drosophila melanogaster is a member of an ancient gene family, defined by the adjacent, region-specific homeotic gene spalt

Abstract: We report the full coding sequence of a new Drosophila gene, spalt-related, which is homologous and adjacent to the region-specific homeotic gene, spalt. Both genes have three widely spaced sets of C2H2 zinc finger motifs, but spalt-related encodes a fourth pair of C-terminal fingers resembling the Xenopus homologue, Xsal-1. The degrees of sequence divergence among all three members of this family are comparable, suggesting that the Drosophila genes originated from an ancient gene duplication. The spalt-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…However, very few data are available in flies about the molecular mechanisms of Sal function, and no comprehensive analysis of Sal/Salr partners and target genes has been carried out yet. Thus, a direct interaction with DNA has only been shown in the case of Salr, which is able to bind an AT-rich sequence in the chorion gene s15 promoter with the central zinc finger domain 3 (Table 2; Shea et al, 1990;Barrio et al, 1996). aspect in the regulation of vertebrate sall genes is the involvement of signalling pathways in different developmental systems.…”
Section: Function Of Sall Proteins In Gene Regulationmentioning
confidence: 99%
“…However, very few data are available in flies about the molecular mechanisms of Sal function, and no comprehensive analysis of Sal/Salr partners and target genes has been carried out yet. Thus, a direct interaction with DNA has only been shown in the case of Salr, which is able to bind an AT-rich sequence in the chorion gene s15 promoter with the central zinc finger domain 3 (Table 2; Shea et al, 1990;Barrio et al, 1996). aspect in the regulation of vertebrate sall genes is the involvement of signalling pathways in different developmental systems.…”
Section: Function Of Sall Proteins In Gene Regulationmentioning
confidence: 99%
“…3A), which lies within the same 252 bp region deleted in kni ri [1] . Although it has been observed that single nucleotide mutations can eliminate endogenous enhancer function (Shimell et al, 1994), such cases are sufficiently rare that it was important, as in the K. Lunde and others (Halder et al, 1998), cut, sal and the vg quadrant element (Guss et al, 2001 (Barrio et al, 1996); Brinker (Brk) [c/tGCCAg/c -green type]: (Rushlow et al, 2001;Zhang et al, 2001). No predicted DNA binding sites were identified in fragment EX for Mad (Kim et al, 1997), Ci (Kinzler and Vogelstein, 1990), or Kni (Small et al, 1996).…”
Section: An L2 Enhancer Element Lies Upstream Of the Knirps Coding Rementioning
confidence: 99%
“…The L2 stripe of kni/knrl-expressing cells forms along the anterior border of a broad domain of cells expressing high levels of the related and functionally overlapping spalt-major (salm) (Kühnlein et al, 1994) and spalt-related (salr) (Barrio et al, 1996) zinc finger transcription factors. A variety of evidence indicates that central domain cells expressing the patterning genes salm and salr (together referred to as sal) induce their anterior neighbors, which express very low levels of sal, to become the L2 primordium (Sturtevant et al, 1997;Lunde et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A number of orthologues have been identified in Drosophila (Barrio et al, 1996), human (Kohlhase et al, 1996, Kohlhase et al, 1999a, Kohlhase et al, 2002, mouse (Ott et al, 1996, Buck et al, 2000, Kohlhase et al, 2002, Xenopus (Hollemann et al, 1996, Onuma et al, 1999, Onai et al, 2004, zebrafish (Camp et al, 2003), chick (Capdevila et al, 1999, Farrell and Munsterberg, 2000, Farrell et al, 2001 and Medaka (Koster et al, 1997). In Drosophila the related genes sal and salr are involved in the determination of the embryonic termini, wing patterning and tracheal branching (Kuhnlein et al, 1994, de Celis and Barrio, 2000, Barrio and de Celis, 2004.…”
Section: Abstract: Chick Csal1 Townes-brocks Syndrome Spalt Heartmentioning
confidence: 99%